Perceived Advantages and Disadvantages of Online Grocery Shopping among Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Participants in Eastern North Carolina - Jilcott Pitts, Stephanie B (Curr Dev Nutr, 2020)
This study's purpose was to qualitatively examine perceived advantages and disadvantages of online grocery shopping among participants (n = 7) in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Initial in-depth, qualitative interviews were conducted, after which participants completed an episode of online grocery shopping, picked up the online order at the store, and completed an in-store shopping episode and a follow-up in-depth interview. Interviews were audio-recorded, transcribed verbatim, and analyzed deductively. Participants stated that in-store impulse purchases occurred at the check-out and cookie aisles and included chips and candy, but sometimes healthier foods such as fruit. Advantages of online grocery shopping included ease, convenience, and saving time. Disadvantages included inadequate substitutions, the online shopping fee, lack of control over selection of perishable goods, and inability to find good deals online versus in the store. Further research is needed to determine how to encourage healthy grocery purchases online.